Benchmarking Local Development Environments: Analyzing the Performance of XAMPP, MAMP, and Laragon - Albert Yakobus Chandra; Putry Wahyu Setyaningsih (Bulletin of Computer Science Research, 2025)
In the rapidly evolving landscape of web application development, the choice of a local development environment significantly influences both productivity and performance. This study aims to benchmark three widely utilized local server solutions—XAMPP, MAMP, and Laragon—through a rigorous performance analysis grounded in information technology principles. By examining critical performance metrics such as load times, resource utilization, scalability, and compatibility with various programming languages and frameworks, we provide a holistic view of each platform's capabilities.Utilizing empirical testing methodologies, including stress testing and response time measurements, this research evaluates the environments under varying workloads to simulate real-world application development scenarios. Additionally, we explore factors such as ease of installation, configuration flexibility, and community support, which are essential for developers in selecting an appropriate development environment. The findings reveal significant differences in performance and user experience among the three platforms, emphasizing the implications of server performance on developer efficiency, project timelines, and overall software quality. This study contributes to the body of knowledge in the information technology field by providing actionable insights for practitioners, educators, and researchers. Ultimately, it serves as a foundational resource for informed decision-making regarding local development environments in web application projects, fostering a deeper understanding of how these tools impact the software development lifecycle.